Diversity, equity, and inclusion insights in practice - King, Eden; Roberson, Quinetta M.; Hebl, Michelle R. (Research in social issues in management, 2024)
"This volume of Research on Social Issues in Management, the sixth in the series, presents the unique insights of diversity, equity, and inclusion (DEI) professionals. These individuals--experts and leaders in the DEI field-describe the challenges and opportunities of ideating, implementing, and sustaining DEI work in organizations. Their ideas and experiences offer new solutions for DEI practice as well as new directions for DEI research. Together, these contributions move beyond emergent politicized rhetoric about DEI in organizations toward avenues for building more diverse, equitable, inclusive, and effective organizations"--